2008
DOI: 10.1016/j.knosys.2008.03.005
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on sea water quality prediction

Abstract: This paper studies the problem of predicting future values for a number of water quality variables, based on measurements from under-water sensors. It performs both exploratory and automatic analysis of the collected data with a variety of linear and nonlinear modeling methods. The paper investigates issues, such as the ability to predict future values for a varying number of days ahead and the effect of including values from a varying number of past days. Experimental results provide interesting insights on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 8 publications
1
29
0
1
Order By: Relevance
“…Lead is the number of the intermediate days between the last day used for generating the attributes and the day we are going to predict the target variable. Based on the findings of a previous study [19] we set the window to 9 and the lead to 2.…”
Section: Data Pre-processingmentioning
confidence: 99%
“…Lead is the number of the intermediate days between the last day used for generating the attributes and the day we are going to predict the target variable. Based on the findings of a previous study [19] we set the window to 9 and the lead to 2.…”
Section: Data Pre-processingmentioning
confidence: 99%
“…7,17,18 In applied¯sheries, prediction of water quality is necessary for the assessment of¯sh stocks. 20 For water sustainability, it is important to monitor and predict di®erent water quality variables.…”
Section: Introductionmentioning
confidence: 99%
“…18 Prediction of water quality is also used in decision-making purposes for water resource management. 7 In predicting water quality variables, di®erent statistical methods (e.g. ARIMA, Linear transfer function) are used.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an empirical study on sea water quality prediction can be found in [7]. Hatzikos et al faced the problem of forecasting water quality based on underwater sensors measurements, by means of a large variety of both linear and nonlinear methods.…”
Section: Introductionmentioning
confidence: 99%